Carcass composition and meat quality of Czech genetic resources of nutrias (Myocastor coypus) - Tůmová, E.; Chodová, D.; Svobodová, J.; Uhlířová, L.; Volek, Z. (Czech Journal of Animal Science, 2015)
The effects of sex and colour type on carcass composition, nutrients content, and muscle fibre characteristics of hind leg meat of nutrias raised under intensive conditions were the focus of this study. Thirty-six eight-month-old nutrias of both sexes with three colour types (Standard nutria, ST; Moravian Silver, MS; and Prestice Multicolour, PM) were studied. Live weight was affected by colour type (P < 0.05) and sex (P < 0.001); however, no effects of these variables were found for the dressing out percentage. Crude protein content was significantly higher in males than in females, whereas crude fat content was higher in females. A significant interaction between colour type and sex was found for hydroxyproline and ash contents. Fatty acids were affected primarily by the sex of nutrias. No effect of colour type on the distribution of muscle fibres in the Biceps femoris muscle was found. However, females had fewer βR (P < 0.05) and more αR fibres (P < 0.001) than males.
Keywords: nutria; colour type; slaughter traits; meat nutritional value; muscle fibre